Peculiarities of interregional differentiation in Russia and instruments of its watering-down (Путеводитель предпринимателя, 2020)
In Russia interregional disparities are formed in general by means of some fastest growing regions against the majority ofdepressive territories. Implemented regional policy primary based on the principal of cooperative federalism doesn’t result in convergence of regions. It is more preferable to use the principal of competitive federalism in regional policy to solve the problem of interregional differentiation.